Respuesta :

Answer:

Hence, the value of "x" is -4.

Step-by-step explanation:

[tex]\sf \leadsto \dfrac{2x + 1}{3} + 1 = \dfrac{x - 4}{6}[/tex]

[tex]\sf \leadsto \dfrac{2x + 1 + 3}{3} = \dfrac{x - 4}{6}[/tex]

[tex]\sf \leadsto \dfrac{2x + 4}{3} = \dfrac{x - 4}{6}[/tex]

[tex]\sf \leadsto 6(2x + 4) = 3(x - 4)[/tex]

[tex]\sf \leadsto 12x + 24 = 3x - 12[/tex]

[tex]\sf \leadsto 12x - 3x = -12 - 24[/tex]

[tex]\sf \leadsto 9x = -36[/tex]

[tex]\sf \leadsto x = \dfrac{-36}{9}[/tex]

[tex]\sf \leadsto x = -4[/tex]

Hence, solved!!

Answer:

x=-4

Step-by-step explanation:

[tex] \frac{2x +1 }{3} + 1 = \frac{x - 4}{6} [/tex]

[tex] \frac{2x + 1 + 3}{3} = \frac{x - 4}{6} [/tex]

[tex]6(2x + 4) = 3(x - 4)[/tex]

[tex]2(2x + 4) = x - 4[/tex]

[tex]4x + 8 = x - 4[/tex]

[tex]4x - x = - 4 - 8[/tex]

[tex] 3x = - 12[/tex]

[tex]x = \frac{ - 12}{3} [/tex]

[tex]x = - 4[/tex]